Management of Leaf Blight of Garlic with Fungicides in Central Tarai of Nepal - Chaurasia, Prem C.P.; Prasad, Jang B.; Mandal, Aanandi (Nepal Agriculture Research Journal, 2014)
Management of purple blotch in garlic was carried out in 2005/06 and 2006/07 at horticultural farm of Regional Agricultural Research Station, Parwanipur in Complete Randomized Block Design with three replications. First year’s results indicated insignificant effect of fungicides on Percentage Disease Intensity (PDI) of purple blotch disease of garlic as number of sprays used seemed to be inadequate. Second year’s result revealed that two sprays of Bavistin @ 0.2% had lowest PDI value but at par to other different number of sprays of different fungicides except no spray of fungicide. Bulb yield was highest in two sprays of Dithane M-45 @ 0.3% followed by two sprays of Krinoxyl @ 0.15%, three sprays of Blitox-50 @ 0.3%. Plant height was insignificant and highest bulb weight was found with three sprays of Blitox-50 followed by two sprays of Bavistin. Two year’s combined results indicated that two sprays of Bavistin @ 0.2% had lowest PDI value and all others PDI values were at par except control. The highest bulb yield was given by two sprays of Dithane M-45 followed by three sprays of Bavistin. Plant height and bulb weight were insignificant. It can be recommended that purple blotch disease can be managed by spraying Bavistin @ 0.2% thrice at 15 days interval or any other tested fungicides to have less disease, higher bulb yield and more economic return. Nepal Agric. Res. J. Vol. 8, 2007, pp. 63-66 DOI: http://dx.doi.org/10.3126/narj.v8i0.11582